Herbicidal effects on nodulation, yield and weed control in soybean (Glycine max) - BILLORE, S D; JOSHI, O P; RAMESH, A (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted in rainy season (kharif) 1997 to evaluate the effect of different herbicides on nodulation, dry matter production and weed biomass in soybean. The study revealed that the maximal and minimal nodule number and their dry weight were associated with application of imazethapyr and 2 hand weedings. Application of lactofen as post-emergence did not cause appreciable variation in weed load. Increased dry biomass was observed with application of propaquizafop @ 75 g ai/ha and lactofen @ 90 g ai/ha. Application of imazethapyr @ 100 g ai/ha resulted in maximum yield and was at par with lower dose of imazethapyr, 2 hand weedings and trifluralin.